2021
DOI: 10.1094/pdis-04-20-0898-a
|View full text |Cite
|
Sign up to set email alerts
|

Genome Resource for Peanut Web Blotch Causal AgentPeyronellaea arachidicolaStrain YY187

Abstract: Peyronella arachidicola is the causal agent of peanut (Arachis hypogaea L.) web blotch. Here, we report an assembled draft genome sequence of P. arachidicola strain YY187 obtained from the symptomatic leaf of peanut in China. The genome size is 47.3Mb, consisting of 26 contigs (N50=2.2Mb) with the G+C content of 56.37%. This genome will provide a valuable foundation for further research on genetics and comparative genomics of P. arachidicola.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…P. arachidicola YY187 was used to infect peanut plants. This strain was obtained from peanut leaves with symptoms collected in Yuanyang, Henan, China by single spore isolation and maintained in a −80°C freezer by the Crop Protection Laboratory of Henan Academy of Agricultural Science (Li et al, 2021). To produce the inoculum for infection, P .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. arachidicola YY187 was used to infect peanut plants. This strain was obtained from peanut leaves with symptoms collected in Yuanyang, Henan, China by single spore isolation and maintained in a −80°C freezer by the Crop Protection Laboratory of Henan Academy of Agricultural Science (Li et al, 2021). To produce the inoculum for infection, P .…”
Section: Methodsmentioning
confidence: 99%
“…P. arachidicola YY187 was used to infect peanut plants. This strain was obtained from peanut leaves with symptoms collected in Yuanyang, Henan, China by single spore isolation and maintained in a −80°C freezer by the Crop Protection Laboratory of Henan Academy of Agricultural Science (Li et al, 2021). To produce the inoculum for infection, P. arachidicola mycelium was cultured as a population of spores on oatmeal agar (OA) to induce conidia under alternation of 16 h light and 8 h dark as previously described (Zhang, Zheng, et al, 2019b).…”
Section: Plant and Fungal Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scaffold N/L 50 of the D. glomerata Pj-2 genome is 11/1,359,674 bp, which is far superior than the other two genome assemblies of D. glomerata strains CBS 528.66 (177 scaffolds; N/L 50 = 7/635,919 bp) and M27-16 (946 scaffolds; N/L 50 = 26/469,072 bp). In addition, the Pj-2 genome assembly is either comparable or better than that of other sequenced Didymella species: D. keratinophila 9M1 (577 scaffolds; N/L 50 = 76/141,571 bp), D. heteroderae 28M1 (620 scaffolds; N/L 50 = 38/283,873 bp), D. pinodes WTN-11-157 (1,593 scaffolds; N/L 50 = 91/106,671 bp), D. lethalis GRM-16-623 (512 scaffolds; N/L50 = 50/196,696), D. arachidicola YY187 (25 scaffolds; N/L 50 = 8/2,070,310 bp) ( Li et al., 2021 ); D. exigua CBS 183.55 (176 scaffolds; N/L 50 = 64/145,421 bp), D. rabiei ArMe14 (34 scaffolds; N/L 50 = 9/1,812,190) ( Shah et al., 2020 ) and D. segeticola GZSQ-4 (23 scaffolds; N/L 50 = 6/2,254,797) ( Ren et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, only two draft genome sequences of D. arachidicola have been reported that referred to genome sizes of 34.11 and 47.30 Mb [ 36 , 37 ]. Notably, in one of the draft genome reports (our previous study), the causal fungus of PWB was misused as Peyronellaea arachidicola [ 37 ], which was reclassified as D. arachidicola in 2020 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%